Acute and chronic cardiovascular responses to concentric and eccentric exercise in older adults with knee osteoarthritis - Heather K. Vincent; Sharareh Sharififar; Christian McLaren; James May; Kevin R. Vincent (BMC Sports Science, Medicine and Rehabilitation, 2023)
Abstract Purpose Muscle contraction type in resistance exercise training may confer benefits besides strength in individuals with osteoarthritis and cardiovascular disease (CVD) risks. The purpose of the study was to explore whether Eccentric-resistance training (RT) improved hemodynamic responses to acute walking exercise stress compared to Concentric-RT among individuals with knee OA over four months. Methods This was a secondary analysis from a randomized, controlled, single-blinded study. Participants (N = 88; 68.3 ± 6.4 yrs; 67.4% female) were randomized to one of two work-matched resistance training (RT) programs against a non-RT control group. Pre-training and month four, participants completed a self-paced Six-Minute Walk Test (6MWT) and progressive treadmill exercise test. Heart rates, blood pressures and mean arterial pressures (MAP) were captured during each test. Antihypertensive medications use was documented at each time point. Results Leg strength improved in both training groups by month four (p < .05). Changes in 6MWT distance and progressive treadmill test time were not different across groups over four months. Neither Concentric or Eccentric RT produced different hemodyamic responses during the 6MWT compared to the control group post-training. However, Concentric RT was associated with 6.0%-7.4% reductions in systolic blood pressure during the graded treadmill walking test at 50%, 75% and 100% of the test time compared to Eccentric RT and the controls (p = .045). MAP values were lower at 75% and 100% of the treadmill test after Concentric RT (5.7%-6.0% reductions) compared to Eccentric RT (1.0%-2.4% reductions) and controls (1.5% and 4.0% elevations) post-training (p = .024). Antihypertensive medication use did not change in any group. Conclusions The repeated, progressive exposures of Concentric RT-induced blunted the hypertensive responses to acute exercise compared to Eccentric-RT. Among people with knee OA, Concentric-RT may confer strength benefits to manage OA and possibly reduce cardiovascular stress during exercise.